1996
DOI: 10.1111/j.1476-5381.1996.tb15708.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel antagonist, No. 7943, of the Na+/Ca2+ exchange current in guinea‐pig cardiac ventricular cells

Abstract: other currents as a competitive inhibitor with external Ca2+. This effect is in contrast to DCB which preferentially inhibits the inward rather than the outward Na+/Ca2+ exchange current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
212
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(229 citation statements)
references
References 38 publications
13
212
1
3
Order By: Relevance
“…Pharmacological treatments commonly used for blocking reverse NCX-mediated Ca 2ϩ uptake include the removal of external Ca 2ϩ (0 Ca 2ϩ ) and the addition of the isothiourea derivative KB-R7943 at low micromolar concentrations, which preferentially blocks the reverse mode of Ca 2ϩ uptake cata- lyzed by NCX1 (Iwamoto et al 1996;Watano et al 1996). The divalent cation Ni 2ϩ has also been shown to block Ca 2ϩ uptake via NCX1 and NCX2 with an IC 50 of ϳ50 M (Iwamoto and Shigekawa 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological treatments commonly used for blocking reverse NCX-mediated Ca 2ϩ uptake include the removal of external Ca 2ϩ (0 Ca 2ϩ ) and the addition of the isothiourea derivative KB-R7943 at low micromolar concentrations, which preferentially blocks the reverse mode of Ca 2ϩ uptake cata- lyzed by NCX1 (Iwamoto et al 1996;Watano et al 1996). The divalent cation Ni 2ϩ has also been shown to block Ca 2ϩ uptake via NCX1 and NCX2 with an IC 50 of ϳ50 M (Iwamoto and Shigekawa 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In 1996, Watano et al reported that KB-R7943 inhibits I NCX in a direction-dependent manner in guineapig ventricular myocytes (6). In this experiment, a unidirectional outward I NCX was induced by suddenly raising external Ca 2+ in the presence of Na + in the pipette solution, and a uni-directional inward I NCX was induced by suddenly raising external Na + in the presence of Ca 2+ in the pipette solution.…”
Section: Selective Benzyloxyphenyl Ncx Inhibitorsmentioning
confidence: 98%
“…4). KB-R7943 was developed by Kanebo as the first specific NCX inhibitor (5,6) and is now used as an experimental pharmacological tool (56). SEA0400 is the second and more potent NCX inhibitor than KB-R7943 developed by Taisho Pharmaceutical (7).…”
Section: Selective Benzyloxyphenyl Ncx Inhibitorsmentioning
confidence: 99%
“…A Ca 2ϩ -dependent inactivation of stretch-activated channel activity has been described (68), and activation of the delayed rectifier K ϩ current and of the Na ϩ /Ca 2ϩ exchanger is also regulated by intracellular Ca 2ϩ concentration (3,25,59). Thus, besides the effects of substances that block the stretch-activated channels, other substances can modulate the electrophysiological effects of stretch through different mechanisms that affect Ca 2ϩ handling by myocytes.The present study analyzed and compared the acceleration of ventricular fibrillation (VF) activation frequency produced by acute stretch (8) under the influence of three substances: the Na ϩ /Ca 2ϩ exchanger blocker 23,38,67), the ␤-blocker propranolol, and the adenosine A 2 receptor antagonist SCH-58261 (71). In relation to the first of these drugs, the inactivation of the Na ϩ /Ca 2ϩ exchanger results in a decrease in the slow force response to stretch and in the magnitude of Ca 2ϩ transients (69), although there is little information about its effects upon the electrophysiological modifications induced by stretch.…”
mentioning
confidence: 99%